PROBLEMATIKA IMPLEMENTASI KEBIJAKAN PENERTIBAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA (STUDI KASUS DI KAWASAN CAR FREE DAY TAMAN KOTA BATURAJA) - Ryidoh Alhar; Marratu Fahri; Aprilia Lestari; Rakhmat Saleh (Jurnal Riset Multidisiplin Edukasi, 2026)
Car Free Day, which is intended to serve as a space for social, cultural, and recreational activities, has also been utilized by street vendors (PKL) to sell their goods. As an institution responsible for enforcing regional regulations, the Civil Service Police Unit (Satpol PP) often faces various challenges that cause vendors to repeatedly return to trading activities. This study was conducted from September 21 to October 12, 2025, using a descriptive qualitative research method. Data were collected through interviews, observations, and documentation involving informants from Satpol PP, the Housing and Settlement Office (Perkim), the Trade Office (Disperindag), street vendors, and the community. The results of the study indicate that communication among Satpol PP, Perkim, and Disperindag has not been carried out optimally. In addition, relocation facilities for street vendors are not yet available. The implementers’ disposition has not been fully exercised, as Perkim and Disperindag rarely participate directly in enforcement activities. Furthermore, within the bureaucratic structure, there is no specific Standard Operating Procedure (SOP) governing the division of duties among Satpol PP, Perkim, and the Trade Office. To achieve order and comfort in the Car Free Day area of Baturaja City Park, several measures are required, including strengthening communication among Satpol PP, Perkim, and the Trade Office : providing appropriate relocation sites for street vendors; requiring Satpol PP to submit formal requests prior to enforcement actions; and encouraging the local government to establish SOPs that clearly regulate task distribution in managing street vendors within the Car Free Day area of Baturaja City Park.